Financial evaluations of antibiotic stewardship programs—a systematic review - Dik, Jan-Willem H.; Vemer, Pepijn; Friedrich, Alex W.; Hendrix, Ron; Lo-Ten-Foe, Jerome R.; Sinha, Bhanu; Postma, Maarten J. (Frontiers in Microbiology, 2015)
Introduction There is an increasing awareness to counteract problems due to incorrect antimicrobial use. Interventions that are implemented are often part of an Antimicrobial Stewardship Program (ASPs). Studies publishing results from these interventions are increasing, including reports on the economical effects of ASPs. This review will look at the economical sections of these studies and the methods that were used. Methods A systematic review was performed of articles found in the PubMed and EMBASE databases published from 2000 until November 2014. Included studies found were scored for various aspects and the quality of the papers was assessed following an appropriate check list (CHEC criteria list). Results 1233 studies were found, of which 149 were read completely. 99 were included in the final review. Of these studies, 57 only mentioned the costs associated with the antimicrobial medication. Others also included operational costs (n=23), costs for hospital stay (n=18) and/or other costs (n=19). 9 studies were further assessed for their quality. These studies scored between 2 and 14 out of a potential total score of 19. Conclusions This review gives an extensive overview of the current financial evaluation of ASPs and the quality of these economical studies. We show that there is still major potential to improve financial evaluations of ASPs. Studies do not use similar nor consistent methods or outcome measures, making it impossible draw sound conclusions and compare different studies. Finally, we make some recommendations for the future.